Anna Guerra de Jesús: Hagiografía, confesión y pugnas por el fuero interno en el Reino de Guatemala durante el siglo XVIII - Roque Baldovinos, Ricardo (2019)
This work proposes a reading of Vida admirable y prodigiosas virtudes de la sierva de Dios Ana Guerra de Jesús (Guatemala, 1716) by Antonio de Siria, text written for the purpose of backing the possible canonization of Ana Guerra de Jesús. Even if hagiography is a didactic genre, and therefore without an “aesthetic” intentionality, its study allows to understand the cultural processes of the moment. The analysis of its narrative and stylistic devices shows a subtle staging of subjectivity from the Catholic Church stand point. The Church was then concerned in containing the challenge of secular modern culture. This narrative illustrates the strategic significance of the sacrament of confession as a technology of the self that was instrumental to define and control what was called at that time the inner jurisdiction [fuero interno].